The Effectiveness of Corruption Criminal Investigations During the Covid-19 Pandemic by the Police Corruption Crime Unit Polrestabes Palembang - Abdur Roni Satya Pratana (Police Studies Review, 2021)
The phenomenon of corruption has been occurred since Indonesia’s independence until now. All ranks of people are definitely trying to improve the image of the Police in public by being consistent in eradicating criminal acts of corruption. However, we are currently dealing with the Covid-19 Pandemic now, where various stipulated provisions have limited activities including the investigation of corruption crimes by the Corruption Crime Unit of Polrestabes Palembang. This is also the background of this research with the aim of knowing how the implementation of the investigation of corruption in the Covid-19 Pandemic by the Corruption Criminal Unit of Polrestabes Palembang. The research was conducted on 18-30 January 2021 in the Polrestabes Palembang area. This study used a qualitative approach with descriptive analysis research methods, as well as data collection techniques with observation, interviews, observations, and secondary data analysis to provide a descriptive picture. Related with the pandemic at the end of March 2020, an investigations of the first case had been carried out before, only the compilation of the filing that had been P-21. For the second case, the obstacles caused by the Covid-19 Pandemic began to be felt because the suspect in this case had fled and became the People Wanted List (DPO) so that the investigation process was temporarily halted. For the third case, obstacles were encountered due to budget cuts. Researchers also conducted research related to the management process in carrying out investigations, the Corruption Criminal Unit of Polrestabes Palembang was considered not good enough in all its elements because it had not met the criteria, such as for example for human resources, infrastructure and limited budget and was hindered by the Covid-19 Pandemic. Based on the results of the research, the authors suggest maximizing technological progress, in order to support the investigation process and facilitate related parties such as providing training to Unit Members so that investigations are not hampered. In addition, due to budget cuts, the Corruption Criminal Unit should be able to build a relationship with the services of expert witnesses where the relationship prioritizes emotional feelings, so that when asking for help it is not fixed with the nominal money that the Corruption Criminal Unit of Polrestabes Palembang must provide.